Facile acid fermentation extraction of silkworm pupae oil and evaluation of its physical and chemical properties for utilization as edible oil - Lailatul Ferdousi; Mohajira Begum; Mst. Sarmina Yeasmin; Jasim Uddin; Md. Al-Amin Miah; G.M. Masud Rana; Tahmina Akter Chowdhury; Farhana Boby; Bijoy Maitra; Rahat Khan; Talha Bin Emran; Md. Abu Bakar Siddique (Heliyon, 2023)
Considering the increasing demand for edible oil in recent times, their price in the world market is becoming skyrocketing. In this research, we produced cost-effective edible oil from desilked silkworm pupae (Bombyx mori) applying a facile acid fermentation process, for the first time. The extraction was performed using two different types of organic acids, 3% of each acetic and citric acid. The yield of the extracted oil was 3.52 ± 0.23% from fresh silkworm pupae. The produced oil was then characterized physically and chemically to know its suitability to be used as edible oil. The oil was found with a low peroxide and acid value of 4.82 meq/kg and 1.35 mg KOH/g oil, respectively, and comprised of different fatty acids, in which palmitic acid (32.04%) and oleic acid (34.62%) were in large portions among the total fatty acids. Additionally, the extracted oil included linoleic, α-linolenic, and dihomo-gamma-linolenic acid which have health benefits. The oil was rich with minerals such as Iron, Sodium, Potassium, Calcium, Magnesium, Zinc, and Phosphorus with a negligible concentration of toxic elements such as Manganese, Cobalt, Nickel, Copper, Lead, Cadmium, Chromium, Arsenic, and Silver, indicating a good nutritive value of the extracted oil. Overall, the outcomes of all the characterizations showed that the extracted oil could be used as good edible oil and the corresponding acid fermentation extraction process has the potential to be used as an effective oil extraction method for silkworm pupae.